Analysis of the Principal's Role in School-Based Management Implementation Efforts at SD Inpres 1 Tondo - Muzdalifa, Riza; Gagaramusu, Yusdin Bin. M.; Hariana, Kadek; Rizal, Rizal; Guci, Ammar Abdullah Joni (FKIP - Universitas Riau, 2025)
The existence of SBM in schools makes the role of the principal very important in developing and advancing educational institutions, education personnel, and their outputs. This study aims to analyze the role of school principals in implementing School-Based Management (SBM). This research design uses a qualitative approach with the type of field research, this research is descriptive, where researchers will go directly to the field as the main instrument to observe, interview, and document data relevant to the implementation of MBS by school principals as leaders of basic education institutions. Based on the results of research conducted at SD Inpres 1 Tondo, the principal has a very strategic role in implementing School-Based Management (SBM), especially through the realization of key functions such as educator, manager, administrator, supervisor, leader, innovator, and motivator. The implementation of these roles is carried out not only in a formal context, but also in flexible and adaptive approaches according to the internal conditions of the school.